On the compression softening effect of prestressed beams - Khang, Nguyen Van; Dien, Nguyen Phong; Huong, Nguyen Thi Van (Vietnam Journal of Mechanics, 2006)
The main objective of the present paper is to study the transverse vibration of the prestressed beams. The differential equation of the transverse vibration of the Euler-Bernoulli beam is developed, in which the initial axial strain in every cross section of the beam is taken into account, so that the initial normal stress is not equal to zero. We have proposed some formulae to determine the natural frequencies of the prestressed beam. The forced transverse vibration of the beam with a moving external force has been considered. From this it follows compression softening effect of prestressed beams. A detailed comparison between the calculating results for the prestressed and the non-prestressed beam is also presented.